Structural and electrical conduction behaviour of yttrium doped strontium titanate: anode material for SOFC application - Singh S.; Jha P.A.; Presto S.; Viviani M.; Sinha A.S.K.; Varma S.; Singh P. (My University, 2025)
Yttrium (Y3+) doped strontium titanate (YxSr1-xTiO3-δ with x = 0, 0.03, 0.05, 0.08 and 0.10) was synthesized via citrate-nitrate auto-combustion route. The electrical and structural properties of the prepared compositions were investigated to check their suitability as anode material for SOFC application. The XRD patterns of synthesized specimens showed single phase having a crystal structure similar to that of the undoped SrTiO3. Trace amounts of secondary phase were observed in compositions with x ≥ 0.05. The FESEM micrographs of all compositions revealed a non-monotonous behaviour of grain size in YxSr1-xTiO3 system with YST8 as most porous sample among all prepared compositions. The oxygen content in the specimens was also confirmed through XPS analysis. The conductivity values in air and H2 atmosphere were obtained from Nyquist plots in the temperature range of 100–700 °C. From a systematic study, the conduction mechanism was explained on the basis of defect chemistry. Moreover, the chemical stability of samples was checked through XRD patterns with corresponding FESEM micrographs after the conductivity measurements in H2 atmosphere. Results showed that amongst all the prepared samples, Y0.08Sr0.92TiO3 may be proposed as a promising composition as anode material for SOFC application. © 2018 Elsevier B.V.